Infectious syphilis in women and heterosexual men in major Australian cities: sentinel surveillance data, 2011–2019. Issue 5 (28th February 2023) - Carter, Allison; McManus, Hamish; Ward, James S; Vickers, Tobias; Asselin, Jason; Baillie, Greta; Chow, Eric PF; Chen, Marcus Y; Fairley, Christopher K; Bourne, Christopher; McNulty, Anna; Read, Phillip; et al.
Abstract: Objectives: To examine changes in the positive infectious syphilis test rate among women and heterosexual men in major Australian cities, and rate differences by social, biomedical, and behavioural determinants of health. Design, setting: Analysis of data extracted from de‐identified patient records from 34 sexual health clinics participating in the Australian Collaboration for Coordinated Enhanced Sentinel Surveillance of Sexually Transmissible Infections and Blood Borne Viruses (ACCESS). Participants: First tests during calendar year for women and heterosexual men aged 15 years or more in major cities who attended ACCESS sexual health clinics during 2011–2019. Main outcome measures: Positive infectious syphilis test rate; change in annual positive test rate. Results: 180 of 52 221 tested women (0.34%) and 239 of 36 341 heterosexual men (0.66%) were diagnosed with infectious syphilis. The positive test rate for women was 1.8 (95% confidence interval [CI], 0.9–3.2) per 1000 tests in 2011, 3.0 (95% CI, 2.0–4.2) per 1000 tests in 2019 (change per year: rate ratio [RR], 1.12; 95% CI, 1.01–1.25); for heterosexual men it was 6.1 (95% CI, 3.8–9.2) per 1000 tests in 2011 and 7.6 (95% CI, 5.6–10) per 1000 tests in 2019 (RR, 1.10; 95% CI, 1.03–1.17). In multivariable analyses, the positive test rate was higher for women (adjusted RR [aRR], 1.85; 95% CI, 1.34–2.55) and heterosexual men (aRR, 2.39; 95% CI, 1.53–3.74) in areas of greatest socio‐economic disadvantage than for those in areas of least socio‐economic disadvantage. It was also higher for Indigenous women (aRR, 2.39; 95% CI, 1.22–4.70) and for women who reported recent injection drug use (aRR, 4.87; 95% CI, 2.18–10.9) than for other women; it was lower for bisexual than heterosexual women (aRR, 0.48; 95% CI, 0.29–0.81) and for women who reported recent sex work (aRR, 0.35; 95% CI, 0.29–0.44). The positive test rate was higher for heterosexual men aged 40–49 years (aRR, 2.11; 95% CI, 1.42–3.12) or more than 50 years (aRR, 2.36; 95% CI, 1.53–3.65) than for those aged 15–29 years. Conclusion: The positive test rate among both urban women and heterosexual men tested was higher in 2019 than in 2011. People who attend reproductive health or alcohol and drug services should be routinely screened for syphilis.